Prevalence trends and risk factors for allergic rhinoconjunctivitis, asthma and eczema in the UK - Lavanya Diwakar; Anuradhaa Subramanian; Divya K. Shah; Sumithra Subramaniam; Victoria S. Pelly; Sheila Greenfield; David Moore; Krishnarajah Nirantharakumar (Allergy, Asthma & Clinical Immunology)
Abstract Background Allergic rhinoconjunctivitis (ARC), asthma and eczema carry a substantial morbidity. These conditions often co-exist within the same individual and their prevalence can differ based on age, ethnicity and gender. Objectives Using a UK primary care database, we estimated the trends in prevalence over the last decade for ARC, asthma and eczema and associated risk factors. Methods Longitudinal cohort analysis of the health improvement (THIN) database between 1st Jan 2010 and 1st Jan 2019. Logistic regression analysis was used to explore risk factors for diagnosis of these conditions. Results An average of 4.17 million records per year were analysed, 19.4% were children and 49.75% were male. There was an increase in prevalence of ARC, asthma and eczema amongst adults during the study period, whereas ARC and asthma prevalence amongst children has fallen. By 2018, 1:8 adults and 1:14 children had ARC; asthma was diagnosed in 1:7 adults and 1:10 children whereas eczema was diagnosed in 1:6 adults and 1:4 children respectively. There were regional discrepancies in allergy prevalence across the UK. Caucasians generally had the highest rates of asthma and lower rates of ARC compared with other ethnic groups. Having other allergies substantially increases the odds of having asthma, eczema and ARC. Conclusion The population burden of ARC, asthma and eczema in the UK is substantial. These conditions are often associated with other allergies and can, therefore, be complex to manage. These data support calls for improvement of pathways of care for allergy patients in the UK.